Towards net-zero energy school: A case study in Thailand - Chatchawan Chaichana; Panida Thararak; Yuttana Mona (Energy Reports, 2023)
Most of the schools in Thailand consumes electricity, which is available through the national grid. It is nearly impossible for these schools to achieve net-zero energy because of very limited access to the renewable resources. This research explores the possibility of achieving net-zero energy in a school that is located near the Thailand–Myanmar​ boarder. The school utilizes locally available solar energy and hydropower. An appropriated electrification system for the school is proposed. The system consists of 2 sets of PV modules (24 kWp and 30 kWp), 288 kWh LiFePO 4 battery, and an inverter. It was found that the system was able to supply sufficient amount of electricity generated by solar energy and hydropower. The estimated annual diesel consumption was drastically reduced from 10,668 kg to 380 kg. Ultimately, the annual greenhouse gas emissions reduction was estimated at 3650 kg-CO2e. It was concluded that the school could achieve net-zero energy if further energy efficiency is applied.